2015
DOI: 10.1088/0031-9155/60/22/8723
|View full text |Cite
|
Sign up to set email alerts
|

Resolution limits of ultrafast ultrasound localization microscopy

Abstract: As in other imaging methods based on waves, the resolution of ultrasound imaging is limited by the wavelength. However, the diffraction-limit can be overcome by super-localizing single events from isolated sources. In recent years, we developed plane-wave ultrasound allowing frame rates up to 20,000 fps. Ultrafast processes such as rapid movement or disruption of ultrasound contrast agents (UCA) can thus be monitored, providing us with distinct punctual sources that could be localized beyond the diffraction li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 33 publications
0
92
1
Order By: Relevance
“…It is important to note that the work presented in this paper does not aim to investigate the fundamental limit to which a single, linear, point scatterer can be localised with a given localisation method, as has been investigated in other work [28]. The work presented here differs for a number of reasons.…”
mentioning
confidence: 99%
“…It is important to note that the work presented in this paper does not aim to investigate the fundamental limit to which a single, linear, point scatterer can be localised with a given localisation method, as has been investigated in other work [28]. The work presented here differs for a number of reasons.…”
mentioning
confidence: 99%
“…This is in good agreement with the observations reported in Errico et al . [1] and Desailly et al [9]. …”
Section: Discussionmentioning
confidence: 99%
“…[1] proposed a seminal method, ultrasound localization microscopy (ULM), that uses ultrafast ultrasound imaging to record spatially isolated microbubble blinking events from decorrelated microbubble signals that can be generated by microbubble disruption, dissolution and motion. ULM achieved ~λ/10 subwavelength spatial resolution with a wide dynamic range of blood flow speed measurement (1 mm/s to several cm/s) that is Doppler angle-independent [1, 9]. In an in vivo murine brain study, ULM demonstrated visualization of ~10 μm microvessels over the entire depth of the mouse brain (~10 mm) [1].…”
Section: Introductionmentioning
confidence: 99%
“…By localizing spatially isolated microbubbles through multiple frames, super-resolution ultrasound (SR-US) images can be generated. Even at ultrasonic frequencies in the low MHz range, a localization precision of a few micrometers can be achieved [1], [2]. In the absence of sample motion, it is this localization precision that determines the maximum achievable resolution in super-resolution images.…”
Section: Introductionmentioning
confidence: 99%